IMPACT OF HOME ENVIRONMENT ON THE ACADEMIC PERFORMANCE OF STUDENTS IN OWERRI ZONE, IMO STATE, NIGERIA - Blessing Ndubuisi-Evans, Ngozi (African Journal of Social and Behavioural Sciences, 2024)
This study explored how the home environment affects the academic performance of secondary school students in the Owerri Zone of Imo State, Nigeria. It focused on the impact of parental occupation, family size, and family structure on students' educational achievements. This study was delimited to government-owned secondary schools in Owerri Municipal of Imo state, Nigeria. The method adopted for the study was survey research design. The study's population comprised 1,030 respondents, including 64 principals and 966 teachers from 32 public secondary schools in the Owerri Zone of Imo State. A random sample of 206 respondents, representing 20% of the total population, included 32 principals and 174 teachers. Data collection was conducted using a researcher-designed questionnaire. The instrument's face and content validity were established through the review of two experts in measurement and evaluation and educational management and policy from the Faculty of Education at Imo State University, Owerri. Revisions were made based on their feedback prior to final approval. The instrument demonstrated a reliability coefficient of 0.89, determined using Spearman's rank correlation coefficient (Spearman's ρ). Findings revealed that home environment, including parental education, occupation, family size, economic status, and motivation, significantly affects students' academic performance, with supportive and resourceful home settings encouraging better educational outcomes among secondary school students in Owerri Zone. The study recommends that parents should spend time with their children and check their children’s academic work, direct them where necessary, and discuss the academic problems of their children with their teachers or school guidance counsellors so as to detect the student's problems early enough and tackle it before it affects the students.